2021
DOI: 10.1177/23743735211034064
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted and Restored Patient Experience With Transition to New Electronic Health Record System

Abstract: Transitioning from one electronic health record (EHR) system to another is of the most disruptive events in health care and research about its impact on patient experience for inpatient is limited. This study aimed to assess the impact of transitioning EHR on patient experience measured by the Hospital Consumer Assessment of Healthcare Providers and Systems composites and global items. An interrupted time series study was conducted to evaluate quarter-specific changes in patient experience following implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…1 ). The included studies were conducted in two healthcare systems in the midwestern US [ 15 , 16 ] and a single community hospital in Pennsylvania, US [ 17 ]. All three studies used quantitative surveys and the primary outcome for each was patient satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). The included studies were conducted in two healthcare systems in the midwestern US [ 15 , 16 ] and a single community hospital in Pennsylvania, US [ 17 ]. All three studies used quantitative surveys and the primary outcome for each was patient satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 9 quantitative or mixed methods studies reporting the patient perspective, 7 (78%) [ 48 , 51 , 57 , 69 , 84 , 96 , 102 ] used different survey methods (eg, the Hospital Consumer Assessment of Healthcare Providers and Systems [HCAHPS] survey) to quantify “patient experience” using various satisfaction metrics. Of these studies, 57% (4/7) reported a positive association [ 48 , 57 , 69 , 84 ] between EMR and patient satisfaction scores and 43% (3/7) reported no substantial change [ 51 , 96 , 102 ]. In total, 22% (2/9) of the studies [ 67 , 92 ] used hospital outcomes rather than patient feedback, which did not meet our definition of “experience.”…”
Section: Resultsmentioning
confidence: 99%
“…A total of 33% (3/9) of the studies [ 57 , 96 , 102 ] reported patient experience before and after EMR implementation (or transition between EMR systems). Tian et al [ 96 ] surveyed 34,425 patients using the standardized HCAHPS survey and found a significant decreasing trend in patient experience scores for the 6 months after implementation followed by a return to baseline, with no significant changes overall. Monturo et al [ 102 ] surveyed 55 patients and found no significant changes in overall patient satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Their model incorporates people, processes, and technology, and it aims to address the needs of patients [21]. In a study concerning the transition from the old electronic health record system to the new, the measured factors were communication with nurses and doctors, the responsiveness of hospital staff, communication about medication, discharge information, the care transition, and the hospital environment [46]. According to Mayer [31], patients desire convenient, easily accessible care, which can be presented from three perspectives: location, access, and efficiency.…”
Section: Types Of Ehealth Solutions For Patient Usementioning
confidence: 99%
“…(incl. qualitative and/or quantitative questions) [19,20,[22][23][24][25]28,29,34,40,43,46,[52][53][54][56][57][58]60] Interview [30,32,35,37,42,45,59] Focus group [36,41] Service analysis [31,51] Design methods [44] Reviews [26,39,49] Implementation study [18,21,50,61] Cross-sectional study [27,33] eHealth pilot or trial [38,43,47,48,55] The most frequently used method (i.e., surveys) was applied in 18 papers (see Figure 2). As patient satisfaction was one of the most mentioned aspects affecting PX, patient satisfaction surveys were the most broadly applied.…”
Section: Case Studies Qualitative Research Surveysmentioning
confidence: 99%